Utilization of Big Data Analytics to Improve Corporate Environmental Performance in Managerial and Organizational Dimensions - Mardikaningsih, Rahayu; Darmawan, Didit (Bulletin of Science, Technology and Society, 2025)
This research aims to examine how Big Data Analytics (BDAC) capabilities can be utilized to improve corporate environmental performance, particularly within the framework of organizational management and human resources. This research was conducted using a literature-based qualitative approach, examining the contribution of BDAC to the formation of organizational capabilities in data-driven decision making. The findings show that BDAC can strengthen organizational learning, adaptive capabilities, and environmental policy innovation when supported by managerial factors such as leadership support, organizational readiness, and data literacy. In the SME and entrepreneurial sectors, managerial factors have a significant influence on the effectiveness of BDAC implementation in supporting environmental sustainability. This research also highlights the importance of integrating environmental analytics policies, data competency training, and strengthening data governance. BDAC, as a technological tool, also represents managerial transformation that requires the active involvement of all elements of the organization. These findings contribute to academic understanding and policy recommendations in efforts to strengthen data-based sustainable business practices.